MEMENANGKAN HATI GEN Z: Peran Pemasaran Media Sosial, Branding Politik, dan Citra Kandidat Muda dalam Keberhasilan Pemilu di Sumatra Barat - Nadia Edawarma; Dessy Kurnia Sari; Yulia Hendri Yeni (Halu Oleo University, 2025)
Political elections are influenced by various factors, including social, economic, cultural, and individual preferences that shape voter behaviour. Key elements such as party affiliation, candidate characteristics, policy positions, and socioeconomic status significantly contribute to election outcomes. This study aims to identify the key factors influencing political decisions among Generation Z voters, particularly those supporting Cerint Iraloza in the 2024 Legislative Election in West Sumatra. Using in-depth interviews with 30 Generation Z respondents, the research explores driving factors such as social media marketing, candidate image, political branding, and information-seeking behaviour. The findings reveal that social media influence and trust in the candidate are the primary factors guiding voter decisions. Social media serves as the main platform for Generation Z to access political information, engage in discussions, and form opinions about candidates. This study highlights the role of social media in shaping the candidate’s image and how trust and online engagement are key determinants of political decisions among young voters.